2011
DOI: 10.1016/j.yexcr.2011.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Boundaries, junctions and transitions in the gastrointestinal tract

Abstract: Contiguous regions along the mammalian gastrointestinal tract, from the esophagus to the rectum, serve distinct digestive functions. Some organs, such as the esophagus and glandular stomach or the small bowel and colon, are separated by sharp boundaries. The duodenal, jejunal and ileal segments of the small intestine, by contrast, have imprecise borders. Because human esophageal and gastric cancers frequently arise in a background of tissue metaplasia and some intestinal disorders are confined to discrete regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 52 publications
1
44
0
Order By: Relevance
“…Besides the large remodulation of the intestinal epithelium, distinct nutrient metabolism functions occur between duodenal, jejunal and ileal segments, such as the exposition of gastric chyme to pancreatico-biliar secretions and reduction of particles leading to simple sized molecules than can cross the epithelial barrier in the duodenum [34]. In agreement, we reported that duodenum and jejunum presented significantly higher levels of expression for genes that are well know players in protein and lipid metabolism (supplementary Table S3).…”
Section: Discussionsupporting
confidence: 82%
“…Besides the large remodulation of the intestinal epithelium, distinct nutrient metabolism functions occur between duodenal, jejunal and ileal segments, such as the exposition of gastric chyme to pancreatico-biliar secretions and reduction of particles leading to simple sized molecules than can cross the epithelial barrier in the duodenum [34]. In agreement, we reported that duodenum and jejunum presented significantly higher levels of expression for genes that are well know players in protein and lipid metabolism (supplementary Table S3).…”
Section: Discussionsupporting
confidence: 82%
“…The notochord will regress and disappear, while different parts of the somites give rise to structures as distinct as the vertebrae or muscles. However, some boundaries do persist in the adult; for example, that which separates the stomach into two halves (San Roman and Shivdasani, 2011).…”
Section: Examples Of Boundary Formationmentioning
confidence: 99%
“…The forestomach in rodents, for example, develops a stratified squamous epithelium contiguous with the esophageal mucosa and it functions in the storage and mechanical digestion of food. By contrast, the glandular stomach has a simple columnar epithelium and is further divided into the corpus, which secretes acid and digestive enzymes and the antrum, which secretes mucus and certain hormones, particularly gastrin (San Roman and Shivdasani, 2011). To accommodate dietary variations, stomach size and shape vary widely among vertebrate species, and the various functional compartments occupy different fractions of the organ (Fig.…”
Section: Introductionmentioning
confidence: 99%